Inlay of ultrafine Ru nanoparticles into a self-supported Ni(OH) 2 nanoarray for hydrogen evolution with low overpotential and enhanced kinetics - Chen, Qian-Qian; Yang, Xiao; Hou, Chun-Chao; Li, Kai; Chen, Yong (Journal of materials chemistry. A, Materials for energy and sustainability, 2019)
Electrocatalytic water splitting plays a vital role in the hydrogen fuel industry, but suffers from the lack of efficient non-platinum (Pt) hydrogen evolution reaction (HER) catalysts. Metallic Ru has proven to be one of the promising candidates for the HER. However, the syntheses of Ru nanoparticles in previous reports require harsh reaction conditions such as high temperature or very strong external reductants. Herein, we report an extremely simple and mild method to prepare ultra-small Ru nanoparticles in situ inlaid into a Ni(OH) 2 nanoarray grown on Ni foam (Ru/Ni(OH) 2 /NF) through the “spontaneous oxidation-reduction reaction” strategy. In 1.0 M KOH, this self-supported material displays a high HER activity with an overpotential as low as 25 mV to deliver a current density of 10 mA cm −2 , as well as a low Tafel slope of 47 mV dec −1 . When assembled in a device for overall water splitting, it achieves a current density of 10 mA cm −2 at 1.50 V and shows outstanding long-term stability even at 50 mA cm −2 . The present work provides a facile and green strategy to prepare non-Pt HER electrocatalysts and it can be applied to the development of new photo-and electrocatalysts.